Genome-wide analysis of transposable elements in the coffee berry borer Hypothenemus hampei (Coleoptera: Curculionidae): description of novel families - Hernandez-Hernandez, Eric M. [UNESP]; Fernández-Medina, Rita Daniela; Navarro-Escalante, Lucio; Nuñez, Jonathan; Benavides-Machado, Pablo; Carareto, Claudia M. A. [UNESP] (Springer Nature, 2017)
The coffee berry borer (CBB) Hypothenemus hampei is the most limiting pest of coffee production worldwide. The CBB genome has been recently sequenced; however, information regarding the presence and characteristics of transposable elements (TEs) was not provided. Using systematic searching strategies based on both de novo and homology-based approaches, we present a library of TEs from the draft genome of CBB sequenced by the Colombian Coffee Growers Federation. The library consists of 880 sequences classified as 66% Class I (LTRs: 46%, non-LTRs: 20%) and 34% Class II (DNA transposons: 8%, Helitrons: 16% and MITEs: 10%) elements, including families of the three main LTR (Gypsy, Bel-Pao and Copia) and non-LTR (CR1, Daphne, I/Nimb, Jockey, Kiri, R1, R2 and R4) clades and DNA superfamilies (Tc1-mariner, hAT, Merlin, P, PIF-Harbinger, PiggyBac and Helitron). We propose the existence of novel families: Hypo, belonging to the LTR Gypsy superfamily; Hamp, belonging to non-LTRs; and rosa, belonging to Class II or DNA transposons. Although the rosa clade has been previously described, it was considered to be a basal subfamily of the mariner family. Based on our phylogenetic analysis, including Tc1, mariner, pogo, rosa and Lsra elements from other insects, we propose that rosa and Lsra elements are subfamilies of an independent family of Class II elements termed rosa. The annotations obtained indicate that a low percentage of the assembled CBB genome (approximately 8.2%) consists of TEs. Although these TEs display high diversity, most sequences are degenerate, with few full-length copies of LTR and DNA transposons and several complete and putatively active copies of non-LTR elements. MITEs constitute approximately 50% of the total TEs content, with a high proportion associated with DNA transposons in the Tc1-mariner superfamily.
Keywords: Coffee berry borer; De novo TEs annotation; Hypothenemus hampei; Transposable element library